Chapter Representations of labour mobility from China to Italy by worker writer Deng Yuehua - Pedone, Valentina (Studi e saggi, 2023)
Within the many typologies of mobility between China and Italy, labour mobility is the one that is numerically most important, constituting over 80% of Chinese citizens living in Italy. In terms of cultural productivity, however, it is the one that is least represented. While Chinese international students who live in Italy are very active in the visual arts and individuals who reached Italy through other forms of privileged mobility are also well represented by their literary production in Italian or Chinese, immigrants who work in sectors that require lower skills appear to be under-represented as far as their cultural production is concerned. In this chapter, I introduce the work of Deng Yuehua, a migrant from Fujian who arrived in Italy in 1991. Since then he has been working in different factories and sweatshops run by other Chinese migrants while constantly publishing his writings. In the mid-2000s, he started publishing works in Chinese in local Sinophone magazines and newspapers, as well as on the web. I observe how his production revolves around the trope of the youzi 游子, the wanderer, which has a long tradition in his area of origin. Moreover, by drawing on the new mobility studies paradigm, I highlight how through textual analysis of the production by mobile subjects, we can infer knowledge on the implications of specific mobilities that would be hard to gain otherwise. Specifically, Deng Yuehua's work casts an important light on the private and personal dimensions of individuals who are involved in labour mobility flows from Southern China to Italy.